Književna dela v Wikipediji - Šauperl, Alenka (Knjižnica, 2010)
Subject description of fiction in the Slovenian Cooperative On-line Bibliographic Database (COBIB) is still inadequate. Participation in COBIB is granted to librarians who have successfully passed the exam. As a consequence, the number of contributing librarians is limited. However, all Slovenian librarians can collaborate in the Slovenian Wikipedia. Slovenian and foreign library science researchers have proposed the structure of subject description of fiction. An analysis of articles describing nine works of fiction in five wikipedias (English, French, Spanish, Croatian and Slovenian) has shown new characteristics. Drawing on these findings, a suggestion of an optimal structure is made. An article describing a work of fiction should begin with a general introductory statement comprising the name of the author, his/her nationality and genre. Translators and original title should be written if a translation is presented. Illustrators and other contributors, the background and other specific information on the work should be added if relevant. The main body of the text should be structured in the following chapters: 1) contents, 2) collection, 3) reviews and awards, 4) editions and translations, 5) adaptations, 6) see also, 7) links and 8) sources. An "infobox: book" with Slovenian adaptation and relevant categories should be inserted. Copying these Wikipedia articles into the library catalogue would enhance subject description and provide better subject access to fiction.
Keywords: bibliotekarstvo; library science; knjižnični katalogi; vsebinska obdelava; literature; književnost; Croatian Wikipedia; Wikipedija